Exploring Charged Defects in Ferroelectrics by the Switching Spectroscopy Piezoresponse Force Microscopy. Issue 2 (29th December 2021) - Alikin, Denis; Abramov, Alexander; Turygin, Anton; Ievlev, Anton; Pryakhina, Victoria; Karpinsky, Dmitry; Hu, Qingyuan; Jin, Li; Shur, Vladimir; Tselev, Alexander; Kholkin, Andrei
Abstract: Monitoring the charged defect concentration at the nanoscale is of critical importance for both the fundamental science and applications of ferroelectrics. However, up‐to‐date, high‐resolution study methods for the investigation of structural defects, such as transmission electron microscopy, X‐ray tomography, etc., are expensive and demand complicated sample preparation. With an example of the lanthanum‐doped bismuth ferrite ceramics, a novel method is proposed based on the switching spectroscopy piezoresponse force microscopy (SSPFM) that allows probing the electric potential from buried subsurface charged defects in the ferroelectric materials with a nanometer‐scale spatial resolution. When compared with the composition‐sensitive methods, such as neutron diffraction, X‐ray photoelectron spectroscopy, and local time‐of‐flight secondary ion mass spectrometry, the SSPFM sensitivity to the variation of the electric potential from the charged defects is shown to be equivalent to less than 0.3 at% of the defect concentration. Additionally, the possibility to locally evaluate dynamics of the polarization screening caused by the charged defects is demonstrated, which is of significant interest for further understanding defect‐mediated processes in ferroelectrics. Abstract : A novel method to probe the charged defect density using decoupling of the electrostatic and pure piezoelectric contribution to the switching spectroscopy piezoresponse force microscopy signal is introduced. Combining a facile realization, high spatial resolution, and good sensitivity, it provides a powerful tool for researchers to study defect‐mediated phenomena in ferroelectrics at the nanoscale.